Post-translational modifications in sepsis-induced acute kidney injury: mechanisms and perspectives - Song, Lin; Jiang, Wei; Liu, Ke; Wang, Jing; Gong, Weilei; Yu, Jiangquan; Zheng, Ruiqiang (Frontiers in Pharmacology, 2025)
Sepsis-induced acute kidney injury (SA-AKI), a grave clinical issue with a high mortality rate, has impacted millions of individuals worldwide. Sepsis is a syndrome characterized by life-threatening organ dysfunction resulting from a dysregulated host response to infection. Post-translational modifications (PTMs) refer to the chemical alterations that proteins undergo after their synthesis is complete. Various types of PTMs, including phosphorylation, methylation, acetylation, lactylation, and ubiquitination, may play a crucial role in the acute kidney injury (AKI) associated with sepsis by modulating protein function, stability, and interactions. This article highlights the advances in understanding the role of PTMs in the pathogenesis of sepsis-induced acute kidney injury (SA-AKI), addressing existing challenges and offering future perspectives.